2022
DOI: 10.1186/s12913-021-07372-6
|View full text |Cite
|
Sign up to set email alerts
|

Remote interpreting in primary care settings: a feasibility trial in Germany

Abstract: Background Global migration trends have led to a more diverse population in health care services everywhere, which in turn has set off a paradigm shift away from medical paternalism toward more patient autonomy. Consequently, physicians need to provide a more precise patient-centred healthcare. Professional interpreting appears to play a crucial part in tackling the challenges of language barriers adequately. The aim of this study was to conduct process evaluation through the implementing of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In a previous publication, we described the general settings in more detail and provided information on the results of our quantitative evaluation. These results were promising regarding the implementation of remote interpreting services, slightly favouring VR over TR and a control group 29. Meanwhile, this publication conveys the results of the qualitative evaluation.…”
Section: Introductionmentioning
confidence: 62%
“…In a previous publication, we described the general settings in more detail and provided information on the results of our quantitative evaluation. These results were promising regarding the implementation of remote interpreting services, slightly favouring VR over TR and a control group 29. Meanwhile, this publication conveys the results of the qualitative evaluation.…”
Section: Introductionmentioning
confidence: 62%
“…The interpreting service provided professional and licensed interpreters with either a master’s degree in translation studies or a corresponding qualification if such a master’s degree was not available for their language or a judicial certification [ 8 ]. Hence, the statements and questions of the interpreter were coded as patients’ statements and questions.…”
Section: Methodsmentioning
confidence: 99%
“…The patients could present themselves without an appointment during regular consultation hours, depending on the size and occupancy of the FRC. Since 2015 video interpreters have been utilised in medical consultations in Hamburg’s primary care walk-in clinics of first reception centres [ 6 – 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…These financial cost issues are needed by administrators who have the potential power to decide whether to use VMI systems or not, and are thus important in the promotion of VMI service. In Fiedler et al [10], the rate of using VMI was found low even when refugees had huge demands for interpreting service in medical settings, and on-site interpreting was almost impossible for them. As this study found, it was probably due to the vague cost assessment for VMI service in the relevant settings.…”
Section: Review Of Research Designs and Research Findingsmentioning
confidence: 97%
“…It is not certain whether the relatively high number of VMI articles in 2020 was related to COVID-19, given that none of these five articles mentioned the pandemic. In the years of 2021 and 2022, however, four of the six reviewed articles did use the expression "pandemic" and/or "COVID-19" in their main texts [10,11,19,22].…”
Section: Descriptive Statistics On Publication and Citationmentioning
confidence: 99%